(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Limit storage space, high traffic sensor data transfer and power efficient transmission are samples of the challenging issues in the development of Internet of Everything (IoE) apps. This paper tackles these issues by presenting a suggested lossless compression approach according to lightweight operations. The suggested approach is working efﬁciently even with a low-performance equipment. Furthermore, enhancing the sensor node effectively of IoE by minimizing energy exhaustion and resource utilizing. Hence, provision power and expanding the age of IoE devices. The suggested approach is evaluated by using two datasets as a benchmark by calculating compression ratio firstly, on messages between person to person and secondly, on healthcare sensors (HeartRate and Body Temperature) between machine to person pattern of IoE. In two tests, the suggested approach may obtain a significant compression ratio.